2022
DOI: 10.3390/cancers14236000
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Artificial Intelligence System for Real-Time Endoscopic Prediction of Invasion Depth in Early Gastric Cancer

Abstract: We previously constructed a VGG-16 based artificial intelligence (AI) model (image classifier [IC]) to predict the invasion depth in early gastric cancer (EGC) using endoscopic static images. However, images cannot capture the spatio-temporal information available during real-time endoscopy—the AI trained on static images could not estimate invasion depth accurately and reliably. Thus, we constructed a video classifier [VC] using videos for real-time depth prediction in EGC. We built a VC by attaching sequenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Jiang et al concluded that AI-assisted depth diagnosis is more accurate than that of experts, while Xie et al did not find differences on this matter. Kim et al [ 97 ] compared two AI models, one developed from static images and the second from video clips, and concluded that models developed from videos could predict EGC depth invasion more precisely than image-trained models. A recent study [ 98 ] suggests that human–machine cooperation improves performance when compared to the individual results of either one.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Jiang et al concluded that AI-assisted depth diagnosis is more accurate than that of experts, while Xie et al did not find differences on this matter. Kim et al [ 97 ] compared two AI models, one developed from static images and the second from video clips, and concluded that models developed from videos could predict EGC depth invasion more precisely than image-trained models. A recent study [ 98 ] suggests that human–machine cooperation improves performance when compared to the individual results of either one.…”
Section: Future Perspectivesmentioning
confidence: 99%